Clinical prognostic value of RNA viral load and CD4 cell counts during untreated HIV-1 infection--a quantitative review. - Eline L Korenromp (PLoS ONE, 2009)
BACKGROUND:The prognostic value of CD4 counts and RNA viral load for identifying treatment need in HIV-infected individuals depends on (a) variation within and among individuals, and (b) relative risks of clinical progression per unit CD4 or RNA difference. METHODOLOGY/PRINCIPAL FINDINGS:We reviewed these measurements across (a) 30 studies, and (b) 16 cohorts of untreated seropositive adults. Median within-population interquartile ranges were 74,000 copies/mL for RNA with no significant change during the course of infection; and 330 cells/microL for CD4, with a slight proportional increase over infection. Applying measurement and physiological fluctuations observed on chronically infected patients, we estimate that 45% of population-level variation in RNA, and 25% of variation in CD4, were due to within-patient fluctuations. Comparing a patient with RNA at upper 75(th) centile with a patient at median RNA, 5-year relative risks were 1.4 (95% CI 1.2-1.7) for AIDS and 1.5 (1.3-1.9) for death, without change over the course of infection. In contrast, for a patient with CD4 count at the lower 75(th) centile, relative risks increased from 1.0 at seroconversion to maxima of 6.3 (4.4-8.9) for AIDS and 5.5 (2.7-10.1) for death by year 6, when the population median had fallen to 300 cells/microL. Below 300 cells/microL, prognostic power did not increase, due to a narrower CD4 range. CONCLUSIONS:Findings support the current WHO recommendation (used with clinical criteria) to start antiretroviral treatment in low-income settings at CD4 thresholds of 200-350 cells/microL, without pre-treatment RNA monitoring--while not precluding earlier treatment based on clinical, socio-demographic or public health criteria.